ESTUDIO CITONUCLEAR DE LOS LINFOCITOS SANGUINEOS DE LOS LEPROSOS - GONZALEZ GUZMAN, IGNACIO (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1942)
The future of American biology, in both practical and theoretical activities, depends upon the gathering and utilization of knowledge from all sources, from nature, the laboratory, and the field Natural history, taxonomy, morphology, and other of the ol
BOL INST ESTUD MED BIOL
Keywords: ESTUDIO, CITONUCLEAR, LINFOCITOS, SANGUINEOS, LEPROSOS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS